Versatile syntheses of optically pure PCE pincer ligands : facile modifications of the pendant arms and ligand backbones - Pullarkat, Sumod Appukuttan (2015)
A series of chiral C-stereogenic PCP and PCN ligand precursors were prepared in situ from inexpensive achiral starting materials via a simple catalytic asymmetric P–H addition reaction in good overall yields. This facile catalytic method of preparing the ligand backbones renders easy and economical modifications of the electronically crucial para-substituent, chiral functionalities, and donor atoms for different transition metal ions. A one-pot synthetic procedure was used efficiently to prepare the corresponding optically pure pincer complexes. All the new complexes were characterized by NMR and mass spectroscopy. The molecular structures of several selected complexes have also been elucidated by X-ray crystallography. Preliminary studies indicated that minor structural changes on these novel pincer complexes affect their chemical properties significantly when they were applied as catalysts for the reaction between diphenylphosphine and chalcone.